Canadian tuberculosis health care workers' perspectives on education and counselling for patients and family members who are born outside of Canada - Nancy Bedingfield; Bonnie Lashewicz; Dina Fisher; Kathryn King-Shier (Taylor & Francis Group, 2023)
Tuberculosis health care workers (TB HCWs) in low incidence settings have important perspectives on providing TB education and counselling to patients and family members born in other countries. The purpose of this qualitative study was to explore HCWs' perspectives on barriers and facilitators for capacity-building education and counselling with patients and family members born outside of Canada experiencing advanced infectious TB in Calgary, a city in western Canada. Data were collected through semi-structured interviews and field notes and thematically analysed. Twenty-four HCWs representing clerical staff, nurses, physicians, and allied health professionals employed in TB care were interviewed. HCWs described how multi-level barriers such as patients' fear of death, complex intra-family communication, information-laden appointments, and patients' precarious employment collided resulting in overwhelmed patients and reduced connection to family. Some HCWs were unsure how to discuss TB stigma with patients and family members. HCWs perceived that increased continuity of care and providing patients and family members with digestible amounts of information earlier were important steps towards better practice. HCWs identified that patients and families could benefit from preparation for initial appointments, increased continuity, and improved patient education materials. HCWs should also receive skills-training to facilitate individual and family counselling.